Chemical variables - stream from Erken Catchment, Norra Järsö, 2006-01-17–2013-12-17 - Erken Laboratory (Uppsala University, 2023)
Manual grab samples from the stream for chemical analysis are taken on a biweekly basis during ice-free conditions, and on a monthly basis in the presence of stream ice.
Erken Laboratory (2023). Chemical variables - stream from Erken Catchment, Norra Järsö, 2006-01-17–2013-12-17 [Data set]. Swedish Infrastructure for Ecosystem Science (SITES). https://hdl.handle.net/11676.1/8n-HyDmnflCLoJFOBQ8xifqE
Keywords: Erken Laboratory; Stream; Time instant; Time instant; pH; pH; Phosphate-P; Phosphate-P; Ammonium-N; Ammonium-N; Nitrite-N/Nitrate-N; Nitrite-N/Nitrate-N; Total nitrogen; Total nitrogen; Total organic carbon; Total organic carbon; Soil Science; Markvetenskap; Agriculture, Forestry and Fisheries; Jordbruk, skogsbruk och fiske; Agricultural Science; Jordbruksvetenskap; Ecology; Ekologi; Multidisciplinary Geosciences; Multidisciplinär geovetenskap; Environmental Sciences; Miljövetenskap; Climate Science; Klimatvetenskap